Recent Developments of Transition Metal Compounds-Carbon Hybrid Electrodes for High Energy/Power Supercapacitors - Ren, Kang; Liu, Zheng; Wei, Tong; Fan, Zhuangjun (Nano-Micro Letters, 2021)
Due to their rapid power delivery, fast charging, and long cycle life, supercapacitors have become an important energy storage technology recently. However, to meet the continuously increasing demands in the fields of portable electronics, transportation, and future robotic technologies, supercapacitors with higher energy densities without sacrificing high power densities and cycle stabilities are still challenged. Transition metal compounds (TMCs) possessing high theoretical capacitance are always used as electrode materials to improve the energy densities of supercapacitors. However, the power densities and cycle lives of such TMCs-based electrodes are still inferior due to their low intrinsic conductivity and large volume expansion during the charge/discharge process, which greatly impede their large-scale applications. Most recently, the ideal integrating of TMCs and conductive carbon skeletons is considered as an effective solution to solve the above challenges. Herein, we summarize the recent developments of TMCs/carbon hybrid electrodes which exhibit both high energy/power densities from the aspects of structural design strategies, including conductive carbon skeleton, interface engineering, and electronic structure. Furthermore, the remaining challenges and future perspectives are also highlighted so as to provide strategies for the high energy/power TMCs/carbon-based supercapacitors. Highlights: 1 The development of transition metal compounds-carbon hybrid electrodes for high energy/power supercapacitors is summarized. 2 Effects of the conductive carbon skeleton, interfacial engineering, and electronic structure for transition metal compounds-carbon hybrid are discussed. 3 Some perspectives and issues in the future are provided.